Magnetic core-shell nanoparticles for Hyperthermia: A numerical study of soft and hard core-shell magnetic materials in liver tissue based on dual phase lag model - M. Moshtagh; M. Servatkhah; S. Hosseini; Gh Solookinejad (Biochemistry and Biophysics Reports, 2025)
In this article, local hyperthermia using core-shell magnetic nanoparticles based on soft and hard magnetic ferrite phases, comprising Zn 0.4Co 0.6Fe 2O 4 @Zn 0.4 Mn 0.6 Fe 2O 4, under the influence of an AC magnetic field, has been numerically investigated to simulate heat distribution and tumor destruction in liver tissue.It is observed that the dual-phase-lag (DPL) model predicts the maximum temperature lower than both the Pennes bioheat and the single-phase-lag (SPL) model. In addition simulation of temperature distribution over time considering different core-shell nanoparticles in AC magnetic field, has been performed using DPL model. The highest temperature is related to Zn 0.4 Co 0.6 Fe 2O4 @Zn 0.4 Mn 0.6 Fe 2O4 and the lowest temperature is related to MnFe2O4.We have concluded that these combinations maximize the properties of magnetic nanoparticles and have higher SLP values and more power dissipation of magnetic nanoparticles compared to magnetic nanoparticles of MnFe2O 4, MnFe2O4 @ CoFe2O4 and CoFe2O4 @MnFe2O4.Two-dimensional temperature distribution simulation over time in liver tissue has been performed using DPL model to quantitatively investigate the tumor temperature in different locations. The results show that temperature curves is a Gaussian-like distribution. The temperature curve is symmetric around the y axis. Temperature is maximum at the center of the tumor and decreases radially outward.